2011
DOI: 10.1093/eurpub/ckr168
|View full text |Cite
|
Sign up to set email alerts
|

A study of the prevalence of adverse events in primary healthcare in Spain

Abstract: In spite of an AE being less damaging in PC, large numbers of patients and professionals suffer their consequences each year. An awareness of the magnitude and impact of AE is the first step on the road to the cultural change necessary for achieving safer healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
1
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 19 publications
9
72
1
20
Order By: Relevance
“…12,14,33,34 It is especially noteworthy that doctor-patient communication problems were reported in 10% of the cases in this study, which is similar to the results of a Danish national patient survey, where 10% of all patients reported communication problems. 35 However, no elaboration was given by the GPs.…”
Section: Ethical Approvalsupporting
confidence: 86%
“…12,14,33,34 It is especially noteworthy that doctor-patient communication problems were reported in 10% of the cases in this study, which is similar to the results of a Danish national patient survey, where 10% of all patients reported communication problems. 35 However, no elaboration was given by the GPs.…”
Section: Ethical Approvalsupporting
confidence: 86%
“…In the Organisation for Economic Co-operation and Development’s member countries, 9% of hospitalized patients [1] suffer an adverse event, whereas studies in primary care centers have identified a rate of adverse events of less than 2% for all consultations [3,4]. At hospitals and primary care centers, 18% and 7% of patients, respectively, experienced more than 1 adverse event [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Esto se traduce en 4 millones de pacientes infectados y 40.000 muertes directas atribuibles a las infecciones relacionadas con la asistencia sanitaria, sólo en Europa 1 4 para los hospitales, las infecciones nosocomiales poseen una prevalencia que se sitúa en la media europea (7,1%), con un rango que va del 6,9% al 7,3%. Por otro lado, en el ámbito de la atención primaria de salud, el 7,4% de los eventos adversos que se producen en los centros de salud españoles está relacionado con las infecciones relacionadas con la asistencia sanitaria 5 .…”
Section: Introductionunclassified